Peran Orang Tua dalam Mengembangkan Gaya Belajar Anak menurut Prinsip Alkitabiah di Era Kontemporer - Elisabeth, Laura; Missiani, Ruthy (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
Parents have a great responsibility in instilling Christian values, as emphasized in Proverbs 22:6. However, in the modern era, with increasingly busy lifestyles and ever-evolving technology, parents' involvement in religious education often diminishes, leaving this responsibility to the school or Church. This has led to a decline in the application of Christian values at home. To ensure that children grow up with a strong spiritual foundation, it is important for parents to be actively involved in the child's learning process. The approach used in this study is a literature review, with descriptive analysis using data sources from books, journals and the internet. The results show that active parental involvement in children's education greatly influences the way children learn and develop Christian character. A supportive family environment also plays an important role in shaping children's learning styles, as well as how technology can be used to support Christian education.